2013
DOI: 10.1190/tle32060699.1
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of fiber-optic distributed acoustic sensing (DAS) for subsurface seismic monitoring

Abstract: Nonreflection seismic and inversion of surface and guided waves 936 The Leading Edge June 2013 Nonreflection seismic and inversion of surface and guided waves Field testing of fiber-optic distributed acoustic sensing (DAS) for subsurface seismic monitoring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
195
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(196 citation statements)
references
References 10 publications
0
195
0
1
Order By: Relevance
“…As described in Kazemeini et al [24], in the upper part of the survey, no clear first arrivals could be identified, because of a poorly cemented casing. Casing and cementation of Ktzi202 are shown in Figure 3 (modified after Daley et al [25]). Large parts of the observation well are completed with multiple casings, not cemented to one another or to the formation.…”
Section: Influence Of the Uncementedmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in Kazemeini et al [24], in the upper part of the survey, no clear first arrivals could be identified, because of a poorly cemented casing. Casing and cementation of Ktzi202 are shown in Figure 3 (modified after Daley et al [25]). Large parts of the observation well are completed with multiple casings, not cemented to one another or to the formation.…”
Section: Influence Of the Uncementedmentioning
confidence: 99%
“…[25]). Left: casing and cementation (grey) of Ktzi202; the lithology is plotted in the centre of the well [21].…”
Section: Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibre-optic distributed acoustic sensing technology (DAS) can be used for exploring earth crustal elastic properties and monitoring both strain and seismic waves with unprecedented acquisition characteristics (Daley et al, 2013). The DAS technology principle lies in sending successive and coherent pulses of light in an optical fibre and measuring the back-scattered light issued from elastic scattering at random defaults within the fibre (Massoudi & Newson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…
SUMMARYWe present new results of records from a 15 km long fibre-optic cable deployed at the surface in Iceland.We estimate the quality of records of seismic events with the cable for both exploration and monitoring.EAGE/DGG Workshop on Fibre Optic Technology in Geophysics 31 March 2017, Potsdam, Germany
AbstractThe fibre-optic distributed acoustic sensing technology (DAS) can be used for exploring earth crustal elastic properties and monitoring both strain and seismic waves with unprecedented acquisition characteristics (Daley et al, 2013). The DAS technology principle lies in sending successive and coherent pulses of light in an optical fibre and measuring the back-scattered light issued from elastic scattering at random defaults within the fibre (Massoudi & Newson, 2016).
…”
mentioning
confidence: 99%